ANALISIS HUKUM BANK SEBAGAI LEMBAGA INTERMEDIASI DAN LEMBAGA KEPERCAYAAN - Ratna Syamsiar (Fiat Justisia: Jurnal Ilmu Hukum, 2007)
Bank as an intermediary to channel customer deposits in the form of credit and banking services required to implement the precautionary principle (prudential banking) and signs of health in order to bank in a healthy state. With the implementation of obligations by the bank as an institution of trust as stipulated in Law No. 10 of 1998, Act 23 of 1999 Act No.3 of 2004 and the provisions of BI, customers do not hesitate to save money and use banking services. Thus will be realized the mission of a bank to improve the welfare of society. Keywords: Banks, Institutions Intermediation